2015
DOI: 10.1093/annonc/mdu498
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtype and tumor characteristics of breast cancer metastases as assessed by gene expression significantly influence patient post-relapse survival

Abstract: An enhanced understanding of the biology of breast cancer metastases is needed to individualize patient management. Here, we show that tumor characteristics of breast cancer metastases significantly influence post-relapse survival, emphasizing that molecular investigation at relapse offers clinically relevant information, with the potential to improve patient management and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 17 publications
7
87
0
1
Order By: Relevance
“…2D), there was an overlap between the two groups with a subset of tumors with high ITGB6 expression with no lymph node metastasis and conversely, a few tumors with low ITGB6 expression had metastasized to the lymph node. Further, analysis of the TEX trial data 36 showed that HER2+ metastatic lesions possessed the highest mean expression of ITGB6 mRNA level ( P  < 0.0001, Fig. S3) compared to other PAM50 subtypes, further lending support to integrin β 6‐mediated metastasis in HER2+ tumors.…”
Section: Discussionmentioning
confidence: 82%
“…2D), there was an overlap between the two groups with a subset of tumors with high ITGB6 expression with no lymph node metastasis and conversely, a few tumors with low ITGB6 expression had metastasized to the lymph node. Further, analysis of the TEX trial data 36 showed that HER2+ metastatic lesions possessed the highest mean expression of ITGB6 mRNA level ( P  < 0.0001, Fig. S3) compared to other PAM50 subtypes, further lending support to integrin β 6‐mediated metastasis in HER2+ tumors.…”
Section: Discussionmentioning
confidence: 82%
“…Of note, this short-term cutoff was defined retrospectively to capture the visually apparent distribution in postrelapse BCSS (41% of patients died within 1.5 years) and was determined by applying a model of two normal distributions to the survival time variable. A comprehensive description of this cutoff and associated methods has been previously published (17). To assess differences between primary tumor clinicopathologic variables and metastatic tumor gene-expression subtypes statistical tests were chosen based on the class of variables being compared: ordinal versus nominal (e.g., RS vs. ER)—Wilcoxon/Mann–Whitney test; categorical versus nominal (e.g., PAM50 vs. ER)—χ 2 or Fisher exact tests; categorical versus ordinal—Kruskal–Wallis test; ordinal versus ordinal—Spearman rank correlation test.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that transcriptional pathway activity and the molecular subtypes (PAM50) of breast cancer metastases significantly influence patient postrelapse survival (17). Here, we aim to extend these findings through Kaplan–Meier and Cox regression analysis of five routinely employed gene expression signatures, along with a simple cell-cycle classifier, with specific focus on site of metastatic relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 32% of the metastases were HER2-enriched, 25% basal-like, 10% luminal A and 28% luminal B. (61) Oakman C et al and Rubovszky G et al also reported that Triple negative breast cancer (TNBC) accounts for approximately 15% of breast cancer cases. TNBC occurs in younger women and is marked by high rates of visceral and CNS metastases, relapse and early death.…”
Section: Figure (2)mentioning
confidence: 98%